PERAN INFLUENCER MEDIA SOSIAL DALAM MEMBENTUK CITRA DESTINASI PARIWISATA: PERSPEKTIF KUALITATIF - Santoso, Rudi; Herlina, Amalia (Sintesa, 2025)
In the digital era, social media influencers play a significant role in shaping public perception of tourism destinations. This research aims to explore how the content produced by influencers influences the construction of destination images in the eyes of the audience, specifically through a qualitative approach. Using case study methods and in-depth interviews with several tourism influencers as well as industry observers, this study highlights the visual, narrative, social, and ethical dimensions of communication conducted on social media. The results show that destination images are strongly formed through repetitive aesthetic visualizations and narratives that build authentic and emotional impressions. Influencers not only serve as promotional agents, but also as cultural and social mediators that shape the public's imagination regarding the travel experience. The findings also emphasize the importance of strategic collaboration between tourism industry players and influencers in maintaining a balance between promotion and message authenticity. In addition, ethical aspects such as paid content transparency and social responsibility in shaping public expectations are important issues that need to be considered. This research contributes to the tourism communication literature by highlighting how the role of influencers is evolving into key actors in the destination's digital ecosystem. Practical implications include the need for a collaborative, value-based, and sustainable approach in destination promotion strategies through social media. Keywords: influencers, social media, destination image, tourism communication, qualitative approach, digital communication